(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Quality of life of medical students may influenced by different socio-demographic components and disrupt their capability to study medicine. An in-depth exploration of these elements may encourage enhancement in learning and retention of medical students. Aim: This study was designed to identify the role of socio-demographic factors in quality of life in undergraduate medical students. Material and Method: A cross-sectional study was conducted among 223 undergraduate medical students (male = 125, females = 98) at King Faisal University, Saudi Arabia between February and September 2019. An Arabic version of WHOQOL-BREF was used to explore the QOL of medical students. Regression analysis were employed to evaluate association between QOL and socio-demographic factors including age, sex, academic year, family type, area of residence, monthly income, parental education and housing status. Result: The results showed a significant relationship between various socio-demographic variables and quality of life. The findings of the study revealed that gender, academic year, marital status, monthly income and family type were found significant predictors of quality of life among medical students. Conclusion: The present study has explored the impact of socio-demographic factors on the quality of life of medical students. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.250-257